The Biodiesel Market in Brazil and the Prospects for the Sector - Verdi, Evandro Luis; Gilioli, Rosecler Maschio; Camargo, Maria Emilia; Zanandrea, Gabriela; Motta, Marta Elisete Ventura da; Biegelmeyer, Uiliam Hahn (International Journal of Business, Economics and Management, 2014)
This article aimed to study the biodiesel market in the country and the future prospects for the sector. Thus it was held a bibliographical research on the subject, addressing the concept of biodiesel, the main raw materials used for their production and a brief history of biodiesel in Brazil. The methodology applied in this article was qualitative and exploratory research. Still, in the qualitative phase, was used the strategy of bibliographical research, which according to Marconi and Lakatos (2006), includes bibliography ever published in relation to the subject of study. Data were obtained concerning the advantages and benefits generated by the implementation of the program of biodiesel in Brazil; growth potential of the Brazilian consumer market; future demand based on prospects for national and international economic growth and development and evolution of the biodiesel industry in different regions of the country. At the end one concludes the immediate need of the increase in the percentage of biodiesel in the diesel oil by the Government to keep the industry's progress.